Knowledge value added methodology between theory and application Comparative filed research in some of the Iraqi private banks - الكبيسي, صلاح الدين عواد; عبد الله, حاتم علي (Journal of Economics and Administrative Sciences, 2016)
Abstract        The research to have a clear perceptions about the knowledge value added to assess the knowledge resources of the Iraqi private banks, depending on the value added methodology of the proposed defined (Housel & Bell, 2001), which assumes that the  knowledge value added come through synergetic relationship between knowledge resource and information technology, trying to the possibility of mainstream theory and its application in the Iraqi environment and interpretation of results, and on this basis was launched search of a research problem took root synergetic nature of the relationship between knowledge (human)  resource and information technology, thus achieving the knowledge value added. So it has adopted a search at the entrance deductive derived from positivism (objective) to derive the assumptions of the theoretical framework, and then the possibility of testing a range of cognitive means and verification of objectivity and to make comparisons by content analysis between the three banks are the (Middle East, Commercial Gulf, North) and then strengthened transactions create intellectual value and is based on interviews with half structured (15) as director to determine the learning times as well as the percentage of completion of banking operations through information technology. The results showed the health of the only hypothesis major which proved the availability of return on knowledge to varying degrees among the surveyed banks depending on the operations of the Chairperson, and made it clear indicators occupation of the Gulf Commercial Bank center stage in terms of return on knowledge and plants create intellectual value, while such as the Middle Bank of East second place, while occupied North Bank finished third, and based on that formulated a set of conclusions which recommends the introduction of knowledge as a platform in the banking environment, based on the specificity of each bank.